Euro Area Policies : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This Selected Issues paper discusses the effectiveness of monetary policy in the euro area in the context of the financial crisis, the need for special resolution regimes for financial institutions in the European Union (EU), and the proposed new EU financial stability arrangements. The paper analyzes the European Central Bank's response to the global financial crisis and discusses ways forward. The case for establishing or improving resolution regimes for financial institutions in EU countries is also outlined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet